2017
DOI: 10.1002/cpt.709
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics‐Based Point‐of‐Care Clinical Decision Support Significantly Alters Drug Prescribing

Abstract: Changes in behavior are necessary to apply genomic discoveries to practice. We prospectively studied medication changes made by providers representing eight different medicine specialty clinics whose patients had submitted to preemptive pharmacogenomic genotyping. An institutional clinical decision support (CDS) system provided pharmacogenomic results using traffic light alerts: green/genomically favorable, yellow/genomic caution, red/high risk. The influence of pharmacogenomic alerts on prescribing behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 48 publications
(50 reference statements)
1
72
0
Order By: Relevance
“…Emerging data have been supportive of the pre‐emptive PGx testing approach. By using EMRs and multi‐gene testing platforms, pre‐emptive genotyping is believed to provide an efficient mechanism to improve therapeutic decisions and outcomes based on PGx testing . More efforts are ongoing to try and determine the most suitable strategy for PGx testing and to evaluate whether the pre‐emptive approach is cost‐effective in order to get buy‐in from third‐party payers …”
Section: Discussionmentioning
confidence: 99%
“…Emerging data have been supportive of the pre‐emptive PGx testing approach. By using EMRs and multi‐gene testing platforms, pre‐emptive genotyping is believed to provide an efficient mechanism to improve therapeutic decisions and outcomes based on PGx testing . More efforts are ongoing to try and determine the most suitable strategy for PGx testing and to evaluate whether the pre‐emptive approach is cost‐effective in order to get buy‐in from third‐party payers …”
Section: Discussionmentioning
confidence: 99%
“…Other pharmacist-assisted methods have been implemented in community pharmacies which proved feasible and took little time, but patient understanding and satisfaction were not investigated [16]. Clinical decision support methods have been employed in some primary care practices; however, physicians may not always know how to utilize and incorporate pharmacogenomics decision alerts in their medical decision-making [19]. In one study, only 30% of physicians receiving the alert were inclined to make a change in prescription based on the specific alert, and in another study physicians reported disagreement about who should be responsible for receiving results and providing patient follow-up [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, five large healthcare system–based pharmacogenetics implementation projects of multigene panels, including SLCO1B1 , have reported preliminary or final results: four in the United States (1,200 Patients Project; INdiana GENomics Implementation: an Opportunity for the UnderServed (INGENIOUS); the Marshfield Clinic; and the RIGHT protocol) and one from La Paz University Hospital in Spain ( Table ). Most of these projects are using passive or active CDS in the EHR to support prescriber use of pharmacogenetic results in several different clinically actionable pharmacogenes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies delivering SLCO1B1 results to providers through the EHR without provider initiation have reported providers’ EHR transactional data. For example, the 1,200 Patients Project of more than a dozen drug–gene pairs reported that 69% of 2,279 patient visits over 3 years were associated with a provider log‐in to the pharmacogenetics CDS system within 72 hours . Approximately one third of patients’ active medications had associated pharmacogenetic alerts (0.5% red, 13% yellow, and 21% green); a 10‐month analysis in the first 608 patients reported that providers clicked on 100%, 72%, and 20% of red, yellow, and green alerts, respectively .…”
Section: Resultsmentioning
confidence: 99%